An unusual presentation of neurotized congenital giant melanocytic nevus and type 1 neurofibromatosis: a diagnostic challenge - Low, Qin Jian; Lim, Tzyy Huei; Lee, Ri An; Cheo, See Wee; Mohd Nasir, Noor ‘Ain; Bakrin, Ikmal Hisyam; Yap, Evelyn Wen Yee (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2022)
Among the three subtypes of neurofibromatosis are type 1 and 2 neurofibromatosis and schwannomatosis, von Recklinghausen disease also known as type 1 neurofibromatosis has an autosomal dominant inheritance. It is the commonest form as and presents with numerous café-au-lait macules and neurofibromas. Giant congenital melanocytic nevus (CGMN) on the other hand is characterized by a melanocytic proliferation that present at birth. CGMN develops due to a defective embryonic pigment cell (melanocyte) precursors development and are often present at birth. Giant congenital melanocytic nevus (CGMN) and type 1 neurofibromatosis may occur together rarely. Clinicians should be aware of the rare presentation of both CGMN and type 1 neurofibromatosis in a patient.